PEDAGOGICAL MANAGEMENT IN THE TRAINING OF CIVIL SERVANTS - Кобзев, Ігор; Мельников, Олександр; Косенко, Віктор; Лук’янова, Вікторія (SWorldJournal, 2026)
The purpose of the article is to identify and study the factors that form the content of training sessions, which are inextricably linked with the considered system of goals and are determined by social and personal needs, the need for training and advanc